The Role of Perceived Friendship Self‐efficacy as a Protective Factor against the Negative Effects of Social Victimization. Issue 1 (9th July 2013) - Fitzpatrick, Sally; Bussey, Kay
Abstract This study examined perceived friendship self‐efficacy as a protective factor against the negative effects associated with social victimization in adolescents. The sample consisted of 1218 participants (557 males, age range 12–17 years). Perceived friendship self‐efficacy was associated with lower internalizing scores irrespective of adolescents' social victimization level and with lower externalizing scores at low, but not high, levels of social victimization. Furthermore, the relationship between perceived friendship self‐efficacy and all forms of adjustment did not differ between boys and girls, or between adolescents in both reciprocated and unilateral very best friendships. The role of perceived friendship self‐efficacy as a protective factor amenable to intervention in social bullying at school is discussed.